Fabrication and experimental study of microfluidic device for particle separation using standing surface acoustic waves (SSAW) - Tay, Justin Jun Yang (2016)
In recent years, much research effort in the field of microfluidics has been directed at studying the behaviour of suspended particles when acted upon by surface acoustic waves (SAW). In particular, the use of standing surface acoustic waves (SSAW) has shown great potential in manipulating objects on the microscale. Particle separation has also been reported through the use of SSAW incorporated into microfluidic devices. Applications for this include developing miniaturised (e.g. lab-on-a-chip) systems for biological and chemical analysis. This project focused on the design, fabrication, and experimental testing of a SSAW-based microfluidic device being capable of continuous separation of particles in a microchannel based on size. The phenomenon of particle actuation via SSAW was demonstrated in the device that was fabricated. Separation of dissimilarly-sized polystyrene particles suspended in water medium was also achieved. Numerical simulation was performed by using COMSOL Multiphysics 5.0 to investigate the effects of sheath layer thickness and particle size on separation efficiency of the device. Numerical and experimental findings were then used to propose an improved design and fabrication process of SSAW microfluidic devices.